The unshod horse: A competitive disadvantage in dressage? - Mott, R.; Ellis, J. (DCA Report; Nr. 044, 2014)
Current literature shows that shoeing improves gait quality but at the risk of increasing concussion to the limbs. To make an informed decision on whether to shoe or not, it is important to quantify if the benefit is worth the risk. This was the first study to compare the kinematics of horses that had been conditioned to being either shod or unshod for at least the previous 12 months, thereby looking at the practical implications for performance. The highly significant increases in joint flexion associated with being shod seen in previous studies using non-conditioned horses could not be replicated. Twenty adult Irish Sport Horses used for a range of activities from general riding up to British Dressage Novice dressage (10 shod and 10 unshod) aged 13±3 years, height 164±5 cm and weight 519±34 kg were recorded in trot in hand on a non-waxed fibre/sand arena surface using a high-speed video camera (120 fps) and compared using KinoveaTM gait analysis software. The differences between the two conditions were assessed against 5 previously determined kinematic criteria for gait quality (stride duration, fetlock extension, scapular rotation, elbow flexion and carpal flexion). Additional stride parameters of speed, stride length, maximum hoof vertical displacement and swing duration were also compared, again using KinoveaTM gait analysis software. Each data set was found to be parametric using the Shapiro-Wilk test for normality and was then compared for significance using a 2-tailed independent t-test. Although there was a general trend towards greater joint flexion in the shod horses, the only highly significant differences (P<0.001) were carpal flexion (71±20 unshod compared to 79±40 shod) and maximum hoof vertical displacement (15±4 cm unshod compared to 21±4 cm shod). The key dressage performance related indicators of stride duration, fetlock extension, scapular rotation and elbow flexion showed no significant differences according to foot treatment. Stride length was significantly reduced (P<0.05) with the shod sample (2.67±0.10 m unshod compared to 2.59±0.10 m shod). It was postulated that horses become habituated to the additional weight of shoes which, over time, reduces the initial effects that previous studies have recorded within 1-3 days of being shod for the first time. Having worn shoes for at least 12 months, shod horses did not display a significant difference in 4 of the 5 kinematic variables that correlate best with dressage marks and were therefore viewed as not having a competitive advantage when compared to their unshod counterparts. LP: The performance of a dressage horse is unlikely to be affected by the choice of being either shod or unshod. This is in contrast to the widely held belief that shoeing improves gait quality.